2016
DOI: 10.9775/kvfd.2016.15311
|View full text |Cite
|
Sign up to set email alerts
|

Balık Patojenlerine Karşı Limon (Citrus limon) ve Argan (Argania spinosa) Yağının Antibakteriyel Aktivitesi

Abstract: The main objective of the study was the identification of antibacterial activity of lemon (Citrus limon L.) peel essential oil and argan (Argania spinosa L.) oil against fish pathogenic bacteria. Antibacterial activity was determined against six different fish pathogens (Yersinia ruckeri, Aeromonas hydrophila, Listonella anguillarum, Edwarsiella tarda, Citrobacter freundii and Lactococcus garvieae). Essential oil derived from lemon peel and argan oil were applied against the bacteria using the disc diffusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These lipids play vital roles in cellular processes, such as maintaining cell membrane integrity, protein modification, and signal transduction [ 18 ]. One prominent example of prenol lipid, limonene, found abundantly in Ammodaucus leucotrichus, Citrus limon peel, and Origanum grosii [ 19 ], [ 20 ], [ 21 ], has been recognized for its chemopreventive and chemotherapeutic activities against various cancers. Research indicates that limonene induces apoptosis in cancer cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These lipids play vital roles in cellular processes, such as maintaining cell membrane integrity, protein modification, and signal transduction [ 18 ]. One prominent example of prenol lipid, limonene, found abundantly in Ammodaucus leucotrichus, Citrus limon peel, and Origanum grosii [ 19 ], [ 20 ], [ 21 ], has been recognized for its chemopreventive and chemotherapeutic activities against various cancers. Research indicates that limonene induces apoptosis in cancer cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial effect of C. lemon and A. spinosa essential oils against Y. ruckeri, A. hydrophila and L. garvieae bacterial strains have been studied by Ontas et al (2016). Their results indicated that both essential oils possessed strong antibacterial effects against Y. ruckeri and A. hydrophila whereas weak antibacterial activity was obtained against L. garviea.…”
Section: Discussionmentioning
confidence: 99%
“…However, conscious or unconscious overdose application of antibiotics might improve the resistance of these antibiotics to the bacteria and thereby a reduced efficacy of the drugs. In addition, antibiotics possess a potential risk to consumers and the environment due to their accumulation within the environment and fishes (Harikrishnan et al 2011;Ontas et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the unconscious use of antimicrobial agents in the treatment of fish diseases causes many negative effects on the environment, fish, and human health (Schnick et al, 1997;Dos Santos, 2000). Therefore, herbal products' use to control fish pathogens in aquaculture is an alternative and current practice (Abutbul et al, 2005;Bansemir et al, 2006;Ekici et al, 2011;Haniffa and Kavitha, 2012;Al Laham and Al Fadel, 2014;Turker and Yıldırım, 2015;Ontas et al, 2016;Diler et al, 2017 a,b;Metin et al,2017).…”
Section: Introductionmentioning
confidence: 99%